Kecemasan dengan Alexithymia: Studi Crossectional pada Remaja - Zakiyyah, Brilianti Ghefira; Rokhman , Abdul; Aris, Arifal (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: Alexithymia is a psychological condition characterized by difficulties in recognizing, understanding, and expressing emotions. Low emotional awareness in individuals with high alexithymia levels has been associated with increased aggression and impulsive behavior. This study aims to analyze the relationship between anxiety levels and stress levels with alexithymia among adolescents at SMA Negeri 1 Sekaran.Methods: This study employed a cross-sectional design. The research population consisted of 354 adolescents, with 185 respondents selected through simple random sampling. Data were collected using the Depression Anxiety Stress Scale (DASS) and the Toronto Alexithymia Scale (TAS-20) questionnaires. The collected data were tabulated and analyzed using the Spearman rank correlation test, with a significance level of p < 0.05.Results: Spearman rank correlation test, with a significance level of p < 0.05. The results indicate that 51.4% of adolescents experienced severe anxiety, 45.9% experienced severe stress, and 61.6% exhibited high alexithymia levels. Statistical analysis yielded a p-value of 0.000 (p < 0.05), demonstrating a significant relationship between anxiety levels and alexithymia among adolescents. Similarly, a p-value of 0.000 (p < 0.05) confirms a significant relationship between stress levels and alexithymia.Conclusion: These findings suggested that anxiety and stress strongly influence alexithymia among adolescents, emphasizing the need for preventive measures such as providing social support, fostering friendships, promoting emotional education, and encouraging social engagement with new individuals. Further research is necessary to explore additional factors that may contribute to alexithymia in adolescents.